2022
DOI: 10.1155/2022/8583924
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Emotion Recognition of Violin Playing Based on Big Data Analysis Technologies

Abstract: The rapid development of Internet technology has promoted the vigorous development of the multimedia. As one of the most classic instruments, the violin has been fully developed in its creation, education, and performance. In the face of more and more violin performances, the effective organization and retrieval of these musical works is an urgent problem to be solved, while it is common to classify and organize music based on the emotional properties of the performance. Deep learning is a model based on featu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…It underwent significant development during the Baroque and Classical periods and became the primary tool for many great composers to create music. Violin performance art carries this rich musical heritage and allows audiences to experience the continuation of history and culture through the performance of classic works [1] .…”
Section: The Cultural Connotation Of Violin Performance Artmentioning
confidence: 99%
“…It underwent significant development during the Baroque and Classical periods and became the primary tool for many great composers to create music. Violin performance art carries this rich musical heritage and allows audiences to experience the continuation of history and culture through the performance of classic works [1] .…”
Section: The Cultural Connotation Of Violin Performance Artmentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%